Reasons of Flouting Maxim in Conversation of “Hansel and Gretel The Witch Hunter” Movie: The Study of Gricean Maxim - Ilna Hidayati Hakimah; Andi Muhammad Irawan (Universitas Negeri Padang, 2022)
People sometimes fail to observe maxims so that is called flouting maxim. Grice in Cutting (2002) proposed four types of flouting maxim; they are flouting maxim of quantity, flouting maxim of quality, flouting maxim of relation and flouting maxim of manner. In general, people sometimes do an error communication due to several reasons. Besides that, an error communication is also found in movie script. In this study, the conversation in the movie script became the source of data, and the script of Hansel and Gretel the witch hunter movie was chosen. Additionally, the aim of this study is to find out the reasons for flouting maxim. And then, Leech’s theory is used to classify the reasons for flouting maxim. It is added by Khoravizadeh and Sadehvandi (2011), Goffman (2008) and Donerus (2005) who are conducted the theory of several reasons in flouting maxim. This study used descriptive qualitative method. The data revealed 38 utterances. As a result, the dominant reason of flouting maxim is occurred by avoiding the discussion. The total number is 9 times (23, 68%). Then, the occurrence of the lowest frequency is misleading counterparts. It occurs 1 time (2, 63%)